Anti-HIV Integrase Inhibitors as New Candidates for the Treatment of COVID-19: A Narrative Literature Review - Salari, Sofia; Karbasforooshan, Hedyieh; Hosseinjani, Hesamoddin (Anti-Infective Agents, 2022)
Background: The initial reports of a contagious novel Severe Acute Respiratory Syndrome- Coronavirus-2 (SARS-CoV-2) were proclaimed by Wuhan, Hubei province, China. This pathogen quickly became a health concern due to the World Health Organization's (WHO) alarm of its pandemic essence. Hence, there is an urgent need for efficacious and curative therapy against COVID-19. Objective: Theoretically, repurposing anti-viral drugs, specifically HIV treatments, could help meet the urgent need for treating COVID-19 due to the structural similarities of their critical enzyme substrates. Integrase inhibitors are a category of anti-HIV drugs that inhibit integrase strand transfer. In this review, we investigate the binding affinity and stability of raltegravir, dolutegravir, bictegravir, and elvitegravir in interactions with crucial enzymes of coronavirus. Methods: A literature search was conducted using scientific databases such as Web of Science, Medline (PubMed), Scopus, Google Scholar, and Embase from commencement to September 2020. The most relevant articles regarding the potential effects of integrase inhibitors against COVID-19 were gathered. Ultimately, ten original articles related to the searched terms were selected for this narrative review. Results: Apparently, in addition to the recent drugs prescribed to cure SARS-CoV-2, integrase inhibitors are promising drugs for repurposing in COVID-19 treatment. Several studies on raltegravir, dolutegravir, bictegravir and elvitegravir were conducted using virtual screening to guess either they are effective or not. Encouraging results were mostly reported for raltegravir and dolutegravir. Nevertheless, bictegravir and elvitegravir need more investigations. Conclusion: Further experimental and clinical studies of antiviral drugs are necessary to introduce appropriate treatment options for COVID-19.
Keywords: dolutegravir